A mindset for strategic thinking: developing a concept and measure - Weyhrauch, William Stewart (Kansas State University, 2016)
Developing effective strategic thinkers in an organization requires a dedication to early identification, selection, development, and practice, along with the conceptual understanding and measurement tools to make it happen. In support of this, the current research focused on three objectives: 1) establishing theoretical support across multiple disciplines for the concept of a strategic thinking mindset, 2) developing the Strategic Thinking Mindset Test (STMT) using situational judgment test methodology for the U.S. Army, and 3) evaluating the results of a pilot test of the STMT for reliability and construct validity. The STMT focuses on three characteristics of a strategic mindset: Flexibility, Humility, and Inclusiveness. These characteristics were derived from themes found common to strategic thinking literature across the disciplines of psychology, management, and military science. In all stages of this research, officers and non-commissioned officers of the U.S. Army served as participants. The first three stages involve the development and keying of content for the STMT. A sample of 125 participants provided scenarios in Stage 1. In Stage 2, 75 participants gave feedback on the scenarios and provided realistic response options. In Stage 3, 224 participants rated the response options according to expression of the characteristic and effectiveness. In Stage 4, the pilot version of the STMT was administered to 229 participants, along with several other measures used to establish construct validity evidence. The results of the pilot test revealed that, although there is some evidence supporting the construct validity of the STMT as a three-factor test of flexibility, humility, and inclusiveness, the overall profile of evidence suggests that the construct(s) being measured are unclear. Low inter-item correlations contribute to a low internal consistency in the measure, which further limits the STMT’s use as a predictor. The pilot test revealed interesting results related to cognitive ability, specifically a negative relationship between the mindset and cognitive ability under best/worst response instructions, rather than a positive relationship or no relationship, as was the case under most/least likely response instructions. Future research recommendations are discussed in the areas of SJT development, scoring, format, and the further refinement and measurement of the strategic thinking mindset.
Keywords: Strategic Thinking; Situational Judgment Testing; Strategic Decision Making; Flexibility; Humility; Inclusiveness